2015
DOI: 10.1021/ml5003663
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidinone Nicotinamide Mimetics as Selective Tankyrase and Wnt Pathway Inhibitors Suitable for in Vivo Pharmacology

Abstract: The canonical Wnt pathway plays an important role in embryonic development, adult tissue homeostasis, and cancer. Germline mutations of several Wnt pathway components, such as Axin, APC, and ß-catenin, can lead to oncogenesis. Inhibition of the poly(ADP-ribose) polymerase (PARP) catalytic domain of the tankyrases (TNKS1 and TNKS2) is known to inhibit the Wnt pathway via increased stabilization of Axin. In order to explore the consequences of tankyrase and Wnt pathway inhibition in preclinical models of cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 22 publications
2
63
0
Order By: Relevance
“…Good progress has been made with the tankyrases, and several cell-active, potent, and selective tankyrase inhibitors are now available. 1618 At the same time, attempts have been made to standardize in vitro assay technology and to characterize PARP inhibitors in terms of selectivity. 19,20 However, most PARP inhibitors have yet been profiled only against a handful of family members, rarely including any representative of the mono-ADP-ribosyltransferase subfamily.…”
Section: Introductionmentioning
confidence: 99%
“…Good progress has been made with the tankyrases, and several cell-active, potent, and selective tankyrase inhibitors are now available. 1618 At the same time, attempts have been made to standardize in vitro assay technology and to characterize PARP inhibitors in terms of selectivity. 19,20 However, most PARP inhibitors have yet been profiled only against a handful of family members, rarely including any representative of the mono-ADP-ribosyltransferase subfamily.…”
Section: Introductionmentioning
confidence: 99%
“…A recent high throughput proteomics screen identified the pyrimidinone nicotinamide mimetic, AZ1366, as a potent and selective inhibitor of TNSK1/2 with good bioavailability in mouse and rat and activity within the canonical Wnt pathway in DLD-1 cells (AZ1366 = Compound 9) (28). To confirm that AZ1366 effectively inhibits tankyrase and has activity within the canonical Wnt pathway in lung cancer cells, we treated HCC4006 cells with various concentrations of AZ1366.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work highlighting the role of the tankyrases in the control of canonical WNT signaling has fueled interest in the development of inhibitors to target this enzyme (24). Numerous studies have shown that inhibition of tankyrase can induce cell killing in Wnt-dependent models of colorectal cancer, and the growing body of knowledge on the importance of the Wnt pathway and β-catenin in multiple cancers has stimulated several directed discovery efforts for tankyrase inhibitors (2528). …”
Section: Introductionmentioning
confidence: 99%
“…10 Treatment of DLD-1(APC mutant) cells with 2 inhibits β-catenin phosphorylation and decreases Wnt-mediated gene transcription as shown in a Luciferase reporter assay in APC mutant DLD-1 cells (IC 50 = 0.06 μM). 11 In an acute dose pharmacokinetic/pharmacodynamic (PK/PD) study, treatment of DLD-1/AKT1 overexpressing murine xenografts with 2 (10 mg/kg, PO) resulted in the 20% inhibition of Wnt-mediated luciferase gene transcription at 8 h, and coincided with an unbound drug concentration at the level of the Wnt reporter IC 50 . When tested in disease model studies using a murine DLD-1(APC mut ) xenograft, compound 2 showed limited tumor growth inhibition.…”
mentioning
confidence: 99%